1998
DOI: 10.1074/jbc.273.18.11062
|View full text |Cite
|
Sign up to set email alerts
|

Syringomycin Action Gene SYR2 Is Essential for Sphingolipid 4-Hydroxylation in Saccharomyces cerevisiae

Abstract: The Saccharomyces cerevisiae gene SYR2, necessary for growth inhibition by the cyclic lipodepsipeptide syringomycin E, is shown to be required for 4-hydroxylation of long chain bases in sphingolipid biosynthesis. Four lines of support for this conclusion are presented: (a) the predicted Syr2p shows sequence similarity to diiron-binding membrane enzymes involved in oxygendependent modifications of hydrocarbon substrates, (b) yeast strains carrying a disrupted SYR2 allele produced sphingoid long chain bases lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 53 publications
5
124
0
Order By: Relevance
“…To answer this question, we used a mutant strain that is defective in the conversion of DHS to PHS. In previous studies (27,28), the syr2 mutant strain was shown to be defective in the C-4 hydroxylation of DHS and dihydroceramide to PHS and PHC, respectively, and the SYR2 gene was proposed to encode a lipid hydroxylase. Therefore, we first determined whether the syr2⌬ mutant strain shows defects in the conversion of DHS to PHS in the JK9-3d strain background.…”
Section: Dhs Needs To Be Converted To Phs To Inhibit Growth-tomentioning
confidence: 99%
“…To answer this question, we used a mutant strain that is defective in the conversion of DHS to PHS. In previous studies (27,28), the syr2 mutant strain was shown to be defective in the C-4 hydroxylation of DHS and dihydroceramide to PHS and PHC, respectively, and the SYR2 gene was proposed to encode a lipid hydroxylase. Therefore, we first determined whether the syr2⌬ mutant strain shows defects in the conversion of DHS to PHS in the JK9-3d strain background.…”
Section: Dhs Needs To Be Converted To Phs To Inhibit Growth-tomentioning
confidence: 99%
“…Serine palmitoyltransferase (SPT) catalyzes the decarboxylative condensation of serine with palmitoyl CoA to form 3-KS in the first step of the long-chain-base synthesis pathway. 3-KS is reduced to DHS by Tsc10p (22) and DHS is hydroxylated to PHS by Sur2p (28,29). Addition of 3-KS, DHS, or PHS to the growth medium rescues the lethality of lcb1⌬ or lcb2⌬ mutant cells.…”
Section: Mutations In the Predicted Plp-binding Residues Of Lcb2pmentioning
confidence: 99%
“…Although these biosynthetic steps are common to GlcCer and IPC pathways, these two components are produced by two distinct ceramide synthases in yeast and filamentous fungi [23,26,36,37], suggesting that these two enzymes possess different substrate specificities. During IPC synthesis, the ceramide is hydroxylated at C-4 by Sur2 (also called BasA in filamentous fungi) to form phytoceramide [38]. Alternatively, DHS can be hydroxylated to form the phytosphingosine (PHS) prior the ceramide condensation [38].…”
Section: Inositolphosphoceramidementioning
confidence: 99%
“…During IPC synthesis, the ceramide is hydroxylated at C-4 by Sur2 (also called BasA in filamentous fungi) to form phytoceramide [38]. Alternatively, DHS can be hydroxylated to form the phytosphingosine (PHS) prior the ceramide condensation [38]. In yeast, the C 26 fatty acid moiety contain 0 to 4 hydroxyl groups at C2, C3, C4 and C5 respectively [39,40].…”
Section: Inositolphosphoceramidementioning
confidence: 99%